NANOTECHNOLOGY IN CIVIL ENGINEERING - Ganesh, V. Kartik (European Scientific Journal, ESJ, 2012)
The role of nanotechnology in conceiving of innovative infrastructure systems has potential to revolutionize the civil engineering practice. This paper first presents an overview of nanotechnology and civil engineering in general and their interdisciplinary approach. Further the Nano-materials and their applications in civil engineering field across its different sections are exemplified. The properties like self-sensing, self- rehabilitation, self-structural health monitoring, self-vibration damping, self-cleaning and self-healing are studied. Following this the analysis were carried out in ductile structural composites along with its enhanced properties, low maintenance coatings, better properties of cementitious materials, reduction of the thermal transfer rate of fire retardant and insulation, various nanosensors, smart materials, intelligent structure technology etc. And also the possible consequences regarding its practicality and the most challenging economic factors concerned are discussed briefly. Finally its future trend and potential towards more economical, sustainable & eco-friendly infrastructure having longer durability are elucidated.